Evaluasi Kebijakan Terhadap Pencegahan Limbah Sampah Pelantar Kota Tanjungpinang : Studi Penelitian Dinas Lingkungan Hidup Kota Tanjungpinang - Joko Prasetiya; Alwan Alfiansyah; Anugrah Perkasa (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to evaluate the Tanjungpinang City Environmental Service's policy towards preventing Tanjungpinang City Landfill Waste. Tanjungpinang City is the capital of the Riau Islands province which will be used as a tourist city in the Riau Islands. However, to make this happen, one of the tasks of the Tanjung Pinang city government is to solve the waste problem in the city of Tanjung Pinang, especially the old city of Tanjung Pinang, which is a slum area that has the largest area among other slum settlements in Tanjung Pinang. The research method uses a descriptive approach which is a method that used to describe a phenomenon or event by relying on data and facts found in the field. The purpose of qualitative research with a descriptive approach is to explain and describe phenomena and their characteristics, as well as having a greater tendency towards how it is implemented or the reasons why something happens. The results of the research show that evaluation is very important so that steps are taken so that the policies made are not arbitrary. -To do this, there must be an appropriate regulatory basis in order to get maximum results because sea cleanliness is the main milestone in the Riau Archipelago, where almost 100% of the Riau Archipelago is sea and is a maritime area, therefore the importance of awareness by both the public and the government so that the economy which is based on the needs of communities in coastal areas and small islands as an effort to empower communities to increase community participation and capacity in coastal and small island management, especially in the field of dealing with coastal and marine waste pollution.